Teachers’ Professional Development at Public Campuses: Issues and Challenges (Rupandehi Campus Journal, 2022)
Teacher professional development is the process of becoming competent teacher. It is an opportunity for teachers to share their knowledge and develop new instructional practices. TPD helps to keep academics up-to-date with the changing world and knowledge. The objective of this study was to explore issues and challenges of teacher professional development in public campuses of Nepal. This study was qualitative approach with a phenomenological design. The participants of the study were three teachers of different public campuses of Rupendehi district selected purposively. The study revealed that teachers of public campuses deserve TPD high significance in the sense that it helps teachers develop various kinds of professional skills, knowledge, and new techniques of teaching. However, Public campuses are facing many challenges which include proper management TPD for faculties of their campuses and there is a gap between policies and practices in implementation of TPD in public campuses of Nepal.